Nanoengineered hollow mesoporous silica nanoparticles for the delivery of antimicrobial proteins into biofilms - Chun, Xu; Yan, He; Li, Zhihao; Ahmad Nor, Yusilawati (RSC, 2018)
The delivery of bactericidal proteins into biofilms is challenging. Hollow mesoporous silica nanoparticles with large cone-shaped pores were synthesized to deliver antimicrobial proteins into biofilms and showed enhanced antimicrobial activities. © 2018 The Royal Society of Chemistry.